Light Emission from Low‐Dimensional Pb‐Free Perovskite‐Related Metal Halide Nanocrystals. Issue 4 (1st December 2022) - Ray, Aniruddha; De Trizio, Luca; Zito, Juliette; Infante, Ivan; Manna, Liberato; Abdelhady, Ahmed L.
Abstract: In recent years remarkable progress has been made on developing low‐dimensional perovskite‐related materials. In particular, with the aim of going toward compounds with low toxicity, various low‐dimensional metal halide nanocrystals have been synthesized and investigated. These nanocrystalline compounds crystallize in a plethora of structures and dimensionalities, in many cases with exciting optical properties. Thanks to their photoluminescence emission, which is typically broad and largely Stokes‐shifted, such nanocrystals can find applications in indoor lighting, scintillators and luminescent solar concentrators. In this review, recent developments leading to the improvement/management of light emission from such low‐dimensional metal halide nanocrystals are highlighted and the possible origin of their light emission is discussed. Furthermore, parallels with their bulk counterparts are drawn and an outlook on what is still worth exploring/studying in this field of research is provided. Abstract : Recently, various Pb‐free low‐dimensional perovskite‐related nanocrystals have been reported. Their photoluminescence is mostly broad and largely Stokes‐shifted making them potential candidates for white light‐emitting diodes and scintillators. In this review, the recent developments for the improvement of light emission from these nanocrystals are highlighted and an outlook on what are the main challenges in this field of research is provided.